The linguist ic generation: Logocentric practices in the works of contemporary Russ ian artists (2010–2022) - I. A. Afanaseva (Шаги, 2023)
The article is devoted to a study of the artistic phenomenon of textuality in contemporary Russian art from 2010 to 2022. The works of contemporary artists (Ivan Simonov, Timofey Radya, Vladimir Abikh, Vladimir Logutov, Semyon Motolyants, Mayana Nasybullova), whose creative practices give the text, phrases, words, statements a lead role, are analyzed here. The works of these artists have not yet been studied in detail by art historians, art critics, and culturologists, but nowadays their creations are widely featured at Russian and foreign exhibition halls, auctions, museums and private collections. The article pays special attention to the various art forms and medias — from painting to installation, from photography to street art and performance. It considers various types of connections between the word, its image, object and semantic meanings, and analyzes the dialogues between the verbal and the visual in the Russian contemporary art. Contemporary artists often work with narratology and visual language, subtle linguistic and pictorial categories. The semantic content of many artworks is multilayer and polysyllabic. The author comes to the conclusion that verbal-visual art is an established trend on the Russian art scene, closely related to the Moscow conceptual circle (Ilya Kabakov, Victor Pivovarov, Eric Bulatov, Andrey Monastyrski, Vitaly Komar and Alexander Melamid).